1998
DOI: 10.1089/aid.1998.14.1187
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Protection Induced by Attenuated Simian Immunodeficiency Virus II. Lymphocyte Depletion Does Not Abrogate Protection

Abstract: To determine the role that cellular immune responses play in the protection conferred by vaccination with attenuated SIVmac32H (pC8), we have attempted to deplete macaques of their CD8+ cells prior to challenge with wild-type SIVmac32H (pJ5). In two of four pC8-infected macaques, N109 and N112, a transient partial depletion of CD8+ cells by antibody treatment was achieved. On the day of challenge peripheral CD2+CD4-CD8+ cell counts were reduced by 92 and 95%, respectively, in animals N109 and N112 and their ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 71 publications
2
32
0
Order By: Relevance
“…This study is part of a series that has characterized the early protection against superinfection conferred by inoculation with live nef-attenuated SIVmacC8 (3,5,48,(50)(51)(52). Previously, we showed that protection against acute superinfection with pathogenic, wild-type SIVmacJ5 can be obtained within 21 days of inoculation with live attenuated SIVmacC8, at a time when neutralizing antibodies were not present and limited CD8 ϩ T lymphocyte responses were detected (51).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This study is part of a series that has characterized the early protection against superinfection conferred by inoculation with live nef-attenuated SIVmacC8 (3,5,48,(50)(51)(52). Previously, we showed that protection against acute superinfection with pathogenic, wild-type SIVmacJ5 can be obtained within 21 days of inoculation with live attenuated SIVmacC8, at a time when neutralizing antibodies were not present and limited CD8 ϩ T lymphocyte responses were detected (51).…”
Section: Discussionmentioning
confidence: 99%
“…Although peripheral CD8 ϩ T lymphocytes are effectively (Ͼ99%) depleted within 1 h of anti-CD8 MAb treatment, the majority of CD8 ϩ lymphocytes are found within lymphoid tissues and have been found to be resistant to effective depletion (23,28,30,52). By increasing the number of anti-CD8 MAb treatments to eight, given over a 3-week period, we were able to effectively deplete lymphoid tissue CD8 ϩ T lymphocytes in naïve macaques and extend greatly the duration of depletion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations